Valorization of eggshell waste as sustainable mechanical reinforcement in biodegradable bio-packaging materials - Amel Gacem; Krishna Kumar Yadav; Zeba Tabassum; Kamal Y. Thajudeen; Mohammed Muqtader Ahmed; Rosalina Ariesta Laeliocattleya; Aniswatul Khamidah; Sri Satya Antarlina; Maha Awjan Alreshidi; F.M. Aldosari; Mosab Kaseem; Chirag Chopra; et al. (Journal of Agriculture and Food Research)
Plastics have long been the dominant material in packaging industries; however, their prevalence is gradually decreasing due to increasing government regulations and growing industry shifts toward eco-friendly alternatives. This transition aims to meet sustainability targets, reduce environmental pollution, and improve brand perception. Although bioplastics are biodegradable and eco-friendly, their mechanical strength, thermal stability, and barrier properties often fall short, limiting their application in advanced packaging that requires durability and low permeability. Concurrently, a large quantity of eggshell waste, rich in calcium carbonate, is discarded in landfills, contributing to environmental pollution. The challenge of managing this waste, along with overcoming the limitations of bioplastics, calls for innovative solutions. This review discusses the potential of eggshell waste as a sustainable material in bio-packaging. It highlights how eggshells can serve as mechanical reinforcements in bioplastics through filler incorporation, transforming them into functional materials such as powders, nanoparticles, and derivatives like calcium oxide, calcium chloride, and calcium carbonate. Biopolymers such as polylactic acid (PLA) and polyvinyl alcohol (PVA) are frequently studied for integrating eggshell-derived materials. These materials significantly improve the mechanical, thermal, and barrier properties of bioplastic films, addressing both environmental and industrial challenges. The review also explores the obstacles and future directions in using eggshell waste in bioplastics, such as compatibility issues, scalability, and the need for optimized processing techniques. These advancements contribute to waste valorization and the development of eco-friendly materials, promoting a circular economy.